Resistance Exercise Attenuates High-Fructose, High-Fat-Induced Postprandial Lipemia - Wilburn, Jessie R (Nutr Metab Insights, 2015)
INTRODUCTION: Meals rich in both fructose and fat are commonly consumed by many Americans, especially young men, which can produce a significant postprandial lipemic response. Increasing evidence suggests that aerobic exercise can attenuate the postprandial increase in plasma triacylglycerols (TAGs) in response to a high-fat or a high-fructose meal. However, it is unknown if resistance exercise can dampen the postprandial lipemic response to a meal rich in both fructose and fat. METHODS: Eight apparently healthy men (Mean ± SEM; age = 27 ± 2 years) participated in a crossover study to examine the effects of acute resistance exercise on next-day postprandial lipemia resulting from a high-fructose, high-fat meal. Participants completed three separate two-day conditions in a random order: (1) EX-COMP: a full-body weightlifting workout with the provision of additional kilocalories to compensate for the estimated net energy cost of exercise on day 1, followed by the consumption of a high-fructose, high-fat liquid test meal the next morning (day 2) (~600 kcal) and the determination of the plasma glucose, lactate, insulin, and TAG responses during a six-hour postprandial period; (2) EX-DEF: same condition as EX-COMP but without exercise energy compensation on day 1; and (3) CON: no exercise control. RESULTS: The six-hour postprandial plasma insulin and lactate responses did not differ between conditions. However, the postprandial plasma TAG concentrations were 16.5% and 24.4% lower for EX-COMP (551.0 ± 80.5 mg/dL × 360 minutes) and EX-DEF (499.4 ± 73.5 mg/dL × 360 minutes), respectively, compared to CON (660.2 ± 95.0 mg/dL × 360 minutes) (P < 0.05). CONCLUSIONS: A single resistance exercise bout, performed ~15 hours prior to a high-fructose, high-fat meal, attenuated the postprandial TAG response, as compared to a no-exercise control condition, in healthy, resistance-trained men.